Moonlighting Intention among Lecturers: The Impact of Career Dissatisfaction and Work Life Balance - Dian Wahyuningsih; Dian Widyantini; Jati Kusuma (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The growing prevalence of moonlighting among university lecturers, driven by career dissatisfaction and work-life balance challenges, has raised concerns about its impact on academic performance and well-being. This study explores the factors influencing lecturers’ intentions to engage in secondary employment, focusing on the interplay between career dissatisfaction and work-life balance. Using a qualitative literature review methodology, the research synthesizes existing studies to examine psychological and structural drivers of moonlighting. The findings reveal that dissatisfaction with career advancement, inadequate compensation, and lack of recognition significantly predict moonlighting intentions, while work-life balance serves as both a negative predictor and a mediating factor between career dissatisfaction and moonlighting. This study uniquely contributes to theory by extending work-life balance frameworks to highlight emotional and mental strain as key drivers in academia, and to practice by offering actionable strategies for institutions. Higher education institutions should address these issues through improved compensation, career development opportunities, recognition, and flexible work policies to reduce moonlighting and enhance faculty satisfaction. These findings underscore the need for targeted interventions to support lecturers’ well-being and institutional productivity, providing a foundation for future research and policy development in academia.